Resolva a equação x+6y=3. X×Y= -9
Soluções para a tarefa
Respondido por
0
x1=
![\frac{9 + 3 \sqrt{17} }{2} \frac{9 + 3 \sqrt{17} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B9+%2B+3+%5Csqrt%7B17%7D+%7D%7B2%7D+)
y1=
![\frac{ - 3 + \sqrt{17} }{4} \frac{ - 3 + \sqrt{17} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+3+%2B++%5Csqrt%7B17%7D+%7D%7B4%7D+)
x2=
![\frac{3 \sqrt{17} - 9 }{2} \frac{3 \sqrt{17} - 9 }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B3+%5Csqrt%7B17%7D+-+9+%7D%7B2%7D+)
y2=
![\frac{ - 3 - \sqrt{17} }{4} \frac{ - 3 - \sqrt{17} }{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+3+-++%5Csqrt%7B17%7D+%7D%7B4%7D+)
y1=
x2=
y2=
Perguntas interessantes